Rapid mutation detection by the Transgenomic wave analyser DHPLC identifies MYOC mutations in patients with ocular hypertension and/or open angle glaucoma. Issue 2 (1st February 2002) - Cobb, C J; Scott, G; Swingler, R J; Wilson, S; Ellis, J; MacEwen, C J; McLean, W H I
Abstract : Aims: To rapidly screen Scottish patients with a family history of open angle glaucoma (OAG) or ocular hypertension (OHT) for mutations in the myocilin gene ( MYOC ) and develop a new rapid screening method for MYOC mutation detection. Methods: All three exons of the MYOC gene were amplified by PCR from genomic DNA and subjected to direct DNA sequencing. Mutation detection methodology was also developed based on denaturing high performance liquid chromatography (DHPLC). A recurrent mutation was investigated by analysis of microsatellite haplotypes at the MYOC gene locus. Results: Mutations were identified by DNA sequencing in four families. MYOC mutation Q368X was found in three kindreds and the fourth family carried the mutation G367R. The Q368X mutation was found to be associated with the same haplotype for markers closely flanking the MYOC gene. The mutations were identified by direct sequencing and were also readily detected by DHPLC analysis of PCR fragments, demonstrating that this is a robust method for MYOC analysis in future. Conclusions: Mutations in the MYOC gene were identified in patients presenting with highly variable phenotypes from normal through OHT to severe OAG. Haplotype analysis showed that mutation Q368X is likely to be an ancestral mutation in this population. DHPLC analysis is an accurate, rapid and cost effective method for MYOC mutation analysis in large population samples.